"3D surface scanner in Maxillofacial Surgery: State of the art." - Í. Aragón Niño; J.L. Del Castillo Pardo de Vera; J.P. Rodríguez Arias; A. Gutiérrez Venturini; J.L. Cebrián Carretero (Elsevier, 2024)
Physicians are used to having complementary studies that help us in all phases of our work. In the maxillofacial surgery field the most commonly used tests are radiological tests (CT and NMR) and digital clinical photographs.In recent years, the concept of 3D surgery has been developed and consists of the use of 3D technology applied to surgery. 3D surgery allows us to move from on-site planning of the surgery to pre-surgical planning, with a simulation and preview of the result at the bone and soft tissue level.Radiological studies are of very limited use in soft tissue planning and digital photography is two-dimensional and dependent on patient positioning. The use of the surface scanner solves these limitations as it computes the spatial coordinates of the patient's anatomical surface in order to create a 3D digital model.